Examining the Effects of Academic Supervision, Work Motivation, and Work Discipline on Teacher Performance - Vicka Rindyani; Ronald Suryaputra; Asriana Kibtiyah (Al-Qalam Institue, 2026)
Teacher performance is a crucial determinant of educational quality as it directly influences instructional effectiveness and student learning outcomes. This study aimed to examine the effects of academic supervision, work motivation, and work discipline on teacher performance. A quantitative correlational design was employed, involving 35 teachers selected through a saturated sampling technique. Data were collected using validated and reliable Likert-scale questionnaires and supported by Teacher Performance Appraisal documentation. The data were analyzed using multiple linear regression. The findings revealed that academic supervision did not have a significant effect on teacher performance (p > .05). In contrast, work motivation had a significant positive effect (p < .05), and work discipline demonstrated the strongest positive influence (p < .05). Simultaneously, the three independent variables significantly predicted teacher performance, indicating that a substantial proportion of variance in performance was explained by the model. These results imply that improving teacher performance requires prioritizing strategies that strengthen work motivation and reinforce work discipline, while enhancing the effectiveness and practical implementation of academic supervision practices.